Disciplinary Background, Educational Level and Information Literacy Skills of Pre-Service Teachers:A Case Study - Kale, Anjali Sandesh (Journal of Information and Knowledge, 2016)
The purpose of this paper is to investigate the information literacy skills of pre-service teachers from teacher education colleges in Mumbai, Maharashtra. The study is also designed to identify the relationship between the discipline and educational level on the information literacy skills of pre-service teachers. Survey method was used to assess the information literacy skills. The population frame consisted of the pre-service teachers from different education colleges in Mumbai. A two stage stratified random sampling technique was used. The sample thus consisted of a total of 386 students from different education colleges in Mumbai. A questionnaire was designed and administered. A causal comparative method was used to study the relationship between discipline and educational level. Data thus collected were analyzed. It was found that a majority of pre-service teachers lacked information literacy skills. Similarly it was found that there is significant difference in the information literacy skills of pre-service teachers from different discipline. It was found that pre-service teachers from science discipline were having high information literacy skills compared to teachers from Arts and Commerce discipline. Whereas there was no difference in their information literacy skills based on their educational level.